The state strikes back : the end of economic reform in China? - Lardy, Nicholas R. (Peterson institute for international economics, 2019)
"The State Strikes Back: The End of Economic Reform in China? examines the reassertion of state control over the Chinese economy, away from the private sector, with an additional focus on why this trend is impeding the country's potential for future economic growth"--